Kemajemukan, Hipotesis Kebudayaan Dominan dan Kesukubangsaan - Parsudi Suparlan (Antropologi Indonesia, 2006)
On the basis of Bruner's concept of a 'dominant culture', the author analyzes the cases of Bandung, Sambas and Ambon. By comparing the three cases, the author reveals the differences of adaptation strategies among the Javanese in Bandung, the Madurese in Sambas, and the BBM (Buton, Bugis, Makassar) in Ambon. The Javanese from the lower classes in Bandung follow the Sundanese culture as the dominant one, and try to adopt Sundanese ways of behavior. Harmonious relationship between the migrants and the Sundanese as the host population is thus maintained. On the other hand, the Madurese in Sambas and the BBM in Ambon forced their rules and principles so as to dominate those from the natives. As a result, conflicts between the natives and the migrants could not be avoided. The author argues that the dominant culture in a specific setting, with its rules and norms, should be followed by the migrants and outsiders. However, the challenges to the dominant culture can be diverse in different societies and settings. The cases in Sambas and Ambon reveal that there is a problem in the challenge toward the dominant culture in those societies. Key words: pluralism; dominant culture; ethnicity.